2005
DOI: 10.1007/s11104-004-5754-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of N losses (NO −3, N 2O, NO) from surface applied, injected or amended (DCD) pig slurry of an irrigated soil in a Mediterranean climate

Abstract: Nitrous oxide (N 2 O), nitric oxide (NO), denitrification losses and NO À 3 leaching from an irrigated sward were quantified under Mediterranean conditions. The effect of injected pig slurry (IPS) with and without the nitrification inhibitor dicyandiamide (DCD) was evaluated and also compared with that of a surface pig slurry application (SPS) and a control treatment (Control) without fertiliser. After application, fluxes of NO and N 2 O peaked from SPS (3.06 mg NO-N m )2 d )1 and 108 mg N 2 O-N m )2 d )1 ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
4
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 33 publications
11
81
4
8
Order By: Relevance
“…The reduction effect of DCD on NO emission may depend on the application rate of DCD, soil character (texture, pH, moisture and temperature), the available NH 4 + concentration, and so on. Under the same application rate of DCD (10%) as ours, Akiyama et al (2015) reported that DCD could reduce 75% of NO emissions in an acid Andosol soil (a volcanic ash soil), whereas Vallejo et al (2005) found that the NO emission was only reduced by 37% with a lower application rate of DCD (5%) into a loam texture soil (pH = 8.1). Because NO emission from field soil is mainly ascribed to nitrification (Zhang et al, 2011;Cui et al, 2012) and negatively correlates to soil moisture (as evidenced by the later NO emission peak from the NP treatment in comparison with N 2 O emission), both the suppression of nitrification by DCD application and the extremely high soil moisture after the fertilization and irrigation in this study favored reduction of NO emission, resulting in the ND treatment having the largest reduction loss rate of NO emission.…”
Section: No Emissionsmentioning
confidence: 47%
See 2 more Smart Citations
“…The reduction effect of DCD on NO emission may depend on the application rate of DCD, soil character (texture, pH, moisture and temperature), the available NH 4 + concentration, and so on. Under the same application rate of DCD (10%) as ours, Akiyama et al (2015) reported that DCD could reduce 75% of NO emissions in an acid Andosol soil (a volcanic ash soil), whereas Vallejo et al (2005) found that the NO emission was only reduced by 37% with a lower application rate of DCD (5%) into a loam texture soil (pH = 8.1). Because NO emission from field soil is mainly ascribed to nitrification (Zhang et al, 2011;Cui et al, 2012) and negatively correlates to soil moisture (as evidenced by the later NO emission peak from the NP treatment in comparison with N 2 O emission), both the suppression of nitrification by DCD application and the extremely high soil moisture after the fertilization and irrigation in this study favored reduction of NO emission, resulting in the ND treatment having the largest reduction loss rate of NO emission.…”
Section: No Emissionsmentioning
confidence: 47%
“…Compared with the NO flux from the NP treatment, the almost identical negative NO fluxes from the CK and ND treatments indicated that the application of DCD could reduce NO loss from the fertilizer application nearly 100%, which was much greater than the percentages (37%-78%) reported in the literature (Meijide et al, 2007;Vallejo et al, 2005;Akiyama et al, 2015). The reduction effect of DCD on NO emission may depend on the application rate of DCD, soil character (texture, pH, moisture and temperature), the available NH 4 + concentration, and so on.…”
Section: No Emissionsmentioning
confidence: 71%
See 1 more Smart Citation
“…No trabalho de Moir et al (2007), a aplicação de DCD (10 kg ha -1 em maio e 10 kg ha -1 em agosto) em uma pastagem com adição de doses elevadas de urina de vacas resultou em aumento médio de 21 % na produção da pastagem. Quando a DCD foi aplicada como inibidor da nitrificação do N amoniacal de dejetos líquidos de suínos (Vallejo et al, 2005) e de bovinos (Tao et al, 2008), o seu efeito foi avaliado apenas sobre as perdas de NO 3 -, N 2 O, NO e NH 3 .…”
Section: Resultados E Discussão Acúmulo De N E Produtividade Do Milhounclassified
“…A incorporação e a injeção dos dejetos no solo podem reduzir a volatilização de NH 3 em pelo menos 90 % (Webb et al, 2010), embora essas possam aumentar as perdas de N por desnitrificação (Wulf et al, 2002). O uso de inibidores de nitrificação no momento da aplicação dos dejetos pode reduzir as emissões de N 2 O (Vallejo et al, 2005;Damasceno, 2010), que podem ocorrer tanto durante a nitrificação do N amoniacal dos dejetos quanto durante a desnitrificação (Arcara et al, 1999). A redução na taxa de nitrificação até que a planta atinja a fase de maior crescimento aumentará a oportunidade dessa em absorver o NO 3 - (Subbarao et (Zaman et al, 2009;Damasceno, 2010).…”
Section: Introductionunclassified